Development and Characterization of Novel Site Specific Hollow Floating Microspheres Bearing 5-Fu for Stomach Targeting - Peeyush Bhardwaj; Deepti Chaurasia; Ranjit Singh; Anoop Swarup (The Scientific World Journal)
Multiple-unit-type oral floating hollow microspheres of 5-fluorouracil (5-Fu) were developed using modified solvent evaporation technique to prolong gastric residence time, to target stomach cancer, and to increase drug bioavailability. The prepared microspheres were characterized for micromeritic properties, floating behavior, entrapment efficiency, and scanning electron microscopy (SEM). The in vitro drug release and floating behavior were studied in simulated gastric fluid (SGF) at pH 1.2. The yield of microspheres was obtained up to 84.46±6.47%. Microspheres showed passable flow properties. Based on optical microscopy, particle size was found to be ranging from 158.65±12.02 to 198.67±17.45 μm. SEM confirmed spherical size, perforated smooth surface, and a hollow cavity inside the microspheres. Different kinetic models for drug release were also applied on selected batches.